Collaboration as Innovation Strategic of Business Resilience Handicraft Industry in Central Java Indonesia - Intan Shaferi; Rio Dhani Laksana; Muliasari Pinilih (AIBPM Publisher, 2022)
Goal: The Covid-19 pandemic has had an impact on the handicraft sector, as efforts to promote it have stalled. Purchase intention is reduced and business is sluggish. This condition provides an idea to be able to innovate in order to maintain the existence of the handcraft business. Practically, the handicraft industry is heavily affected by the declining tourism effect because many of its consumers come from abroad. The traditional nuance is closely related to handicrafts, so many tourists like it. Findings: As a strategy for industry resilience, innovation supports these business people. This research examines how industry players collaborate with many parties and what innovation are being made to deal with the Covid-19 widespread in the business people in the handicraft industry in 2021 in the Central Java region of Indonesia. Results: The results show that innovation with collaboration has an impact on business resilience and gives management strength to be able to make recovery. Supported by government policies, the recovery better. Suggested: the innovation can be deeply focusing on the process and also management to ensure the resilience.Â Keywords: innovation, business strategy, business resilience, handicraft industry.